Diversity, biogeography and host specificity of kelp endophytes with a focus on the genera Laminarionema and Laminariocolax (Ectocarpales, Phaeophyceae). Issue 1 (2nd January 2019) - Bernard, Miriam S.; Strittmatter, Martina; Murúa, Pedro; Heesch, Svenja; Cho, Ga Youn; Leblanc, Catherine; Peters, Akira F.
ABSTRACT: Endophytic filamentous brown algae are known to invade stipes and fronds of kelps with potentially negative effects for the hosts. They have simple filamentous thalli and are difficult to identify based on morphology. We investigated the molecular diversity of 56 endophytes isolated from seven different kelp species from Europe, Chile, Korea and New Zealand by sequencing two unlinked molecular markers (5'COI and ITS1). A majority of 49 of the isolated endophytes (88%) belonged to the genera Laminarionema and Laminariocolax . The endophyte Laminarionema elsbetiae was isolated from Saccharina latissima and S. japonica tissues in Europe and Korea, respectively, and showed highly similar sequences in both regions. Three different species of the genus Laminariocolax were identified, the most common of which was L. aecidioides, an endophyte with a worldwide distribution and a broad host range. The other two species, L. tomentosoides and a species described here as Laminariocolax atlanticus sp. nov., were associated with different kelp species in the northern hemisphere and the North Atlantic, respectively. Our results suggest that specific host-endophyte patterns could exist locally, as found in kelps in Brittany where all endophytes isolated from S. latissima were L. elsbetiae, all endophytes isolated from Laminaria digitata were Laminariocolax tomentosoides, and those isolated from Laminaria hyperborea were Laminariocolax atlanticus and L. aecidioides . However, this pattern was not consistent with the results from other places, such as Western Scotland and Helgoland where the same kelp species are present.